VATAN KONSEPTINING GASTRONOMIK NOMLAR BILAN IFODALANISHI - Xolmo‘minova, M.R. (SCIENCE and SOCIETY, 2024)
The article analyzes and classifies some of the linguistic and cultural concepts, compares them with the concept Homeland, and reveals the relationship between the concepts. Also, in some places, it has been proven that gastronomic names are closely related to the concept Homeland, which means that linguocultures are related to the term.
Keywords: concept; homeland concept; national-cultural concept; linguistic cultures; gastronomic names